2014
DOI: 10.1080/03004430.2013.875543
|View full text |Cite
|
Sign up to set email alerts
|

Supportive family contexts: promoting child well-being and resilience

Abstract: Prevention and intervention programmes for children at risk aim to improve child well-being and resilience. They do so using both direct and indirect strategies, intervening with children but also considering broader contextual factors (such as family dynamics). Children's subjective well-being comprises five main components (physical health, mental health, self-regulation, social competence, and cognitive competence) and is predicted by person, relationship, and contextual factors. Children's resilience, or a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
54
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(61 citation statements)
references
References 60 publications
2
54
0
5
Order By: Relevance
“…Countless studies have found that child well-being is predicted by FWB and parenting quality (McKeown, Pratschke, & Haase, 2003;Newland et al, 2014;Rafferty, Griffin, & Robokos, 2010;Roggman, Boyce, & Innocenti, 2008). When families are struggling, child well-being suffers (Newland, 2014). The purpose of this article is to provide a review of the current literature linking FWB, parenting processes, and child wellbeing.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Countless studies have found that child well-being is predicted by FWB and parenting quality (McKeown, Pratschke, & Haase, 2003;Newland et al, 2014;Rafferty, Griffin, & Robokos, 2010;Roggman, Boyce, & Innocenti, 2008). When families are struggling, child well-being suffers (Newland, 2014). The purpose of this article is to provide a review of the current literature linking FWB, parenting processes, and child wellbeing.…”
mentioning
confidence: 99%
“…Search terms used to select current research for this article included FWB, child well-being, family resiliency, family self-sufficiency, parenting, and child outcomes. Newland (2014) proposed a model of FWB that accounts for a myriad of individual and family-level factors. Collectively, these FWB factors impact parenting opportunities, quality, and outcomes, including child well-being.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Such collaboration can be especially important when preparing intervention programs for adolescent groups or for individuals whose selfexpression and communication in school or with family members are restricted or unsatisfactory. There are programs designed to evolve resilience in school, family or community environment for children and adolescents who are considered at risk or relatively healthy children (see Scales, 2000;Edwards et al, 2007;Wolchik, Schenck, & Sandler, 2009;Juodeikait_ e & Leliugien_ e, 2009;Newland, 2014). Additional resources are needed to prepare special programs intended to contribute to resilience development along with the processes of participation in sport activities designed for coaches, trainers and other sport specialists; this could be direct contribution to adolescent mental health education.…”
Section: Discussionmentioning
confidence: 98%
“…To give context for the study, this paper provides an overview of the assessment of children as well as what is known about the assessment of children in need in Estonia. Tomlinson 2008) and areas for early intervention (Kalland et al 2015;Newland 2014).…”
Section: Introductionmentioning
confidence: 99%